Correlation of Chemerin with Lipid Profile in Blood Women Polycystic Ovarian Syndrome in Tikrit City (Medico Legal Update, 2021)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women ofreproductive age, affecting 6%–10% of women worldwide. Objective: The study aimed to assess the relationof serum chemerin level with lipid profile in women with polycystic ovarian syndrome.Materials and Method: A cross?sectional study was carried out in Salah Al-din City from 10th of October2019, to 20th of December 2019. The number of polycystic ovary syndrome women under study was 60women whose ages were between 15 and 36 years old. These women admitted to obstetrics and gynecologyunit at Salah Al-din Teaching Hospital. The control group who were matched to the patients studied included30 women.Results: The study showed that there is the significant difference between PCOS women and the controlgroup concerning serum chemerin level and lipid profile in PCOS women. This study demonstrates thatthere was a weak positive correlation between levels of chemerin and cholesterol in PCOS women (r =0.02) which is mean that cholesterol level is slightly increased with the elevation of chemerin hormone inwomen with PCOS, There was a positive correlation between levels of chemerin and Triglyceride in PCOSwomen (r = 0.16) which is mean that level is slightly Triglyceride increased with the elevation of chemerinhormone in women with PCOS, There was a positive correlation between serum levels of chemerin andVLDL in PCOS women, slightly VLDL increased with the elevation of chemerin hormone in women withPCOS. There was a positive correlation between levels of chemerin and LDL in PCOS women, slightlyLDL increased with elevation of chemerin hormone in women with PCOS. This study showed negativecorrelation between Chemerin and, HDL in PCOS women, slightly HDL decreased with the elevation ofchemerin hormone in women with PCOS.Conclusion: Highly significant relation of Chemerin and Cholesterol,Triglyceride,LDLandVLDL inPCOS,While negative correlation between Chemerin and HDL